2015
DOI: 10.3390/ma8115431
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assist Extrusion Methods for the Fabrication of Polymer Nanocomposites Based on Polypropylene/Multi-Wall Carbon Nanotubes

Abstract: Isotactic polypropylenes (iPP) with different melt flow indexes (MFI) were used to fabricate nanocomposites (NCs) with 10 wt % loadings of multi-wall carbon nanotubes (MWCNTs) using ultrasound-assisted extrusion methods to determine their effect on the morphology, melt flow, and electrical properties of the NCs. Three different types of iPPs were used with MFIs of 2.5, 34 and 1200 g/10 min. Four different NC fabrication methods based on melt extrusion were used. In the first method melt extrusion fabrication w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…10 −4 S/cm [20], using 30 wt % or higher of graphene. However, the fabrication of iPP/MWCNT with 10 wt % of fillers is important because a high loading of filler can reduce the mechanical properties of PP/CNT [22]. It can be concluded that the fabrication method plays a significantly important role in the AC electrical conductivity, σ (AC) , of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 −4 S/cm [20], using 30 wt % or higher of graphene. However, the fabrication of iPP/MWCNT with 10 wt % of fillers is important because a high loading of filler can reduce the mechanical properties of PP/CNT [22]. It can be concluded that the fabrication method plays a significantly important role in the AC electrical conductivity, σ (AC) , of the material.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Ramasamy [20] prepared polypropylene/graphene nanocomposites and observed negative values of the dielectric constant using amounts of 30%–40% of graphene. It was recently shown that the dispersion of nanoparticles in polymer matrices can be highly enhanced using ultrasound-assisted methods [21,22], thus opening the possibility of reducing the amount of nanoparticles to obtain metamaterial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The CNPs were first sonicated in a glass reactor, to induce the deagglomeration of these carbon nanoparticles [34][35][36], as follows: 1 g of CNPs (CNFs and GPs, as well as the CNFs : GPs mixtures, in the following ratios by weight: 9 : 1, 8 : 2, or 7 : 3) was introduced in a glass reactor arranged with a sonotrode (see Figure 1) and sonicated at 20 kHz for 30 min in an air atmosphere. To improve the efficiency of functionalization, magnetic agitation was included.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the MFI decreases regardless of the method used in processing, the same is not the case with the other properties. For example, as to the size of agglomerates, the smallest value was found using PP of MFI = 2.5 using variable ultrasound frequency in processing; in this sample, it was found a lower surface/agglomerate ratio and a higher value of electrical charge (1040 V) [51]. A similar study showed that the electrical properties in nanocomposites of PP/ MWCNT with different values of MFI of the polymer matrix depend on the methods used in the ultrasound-assisted extrusion because the ultrasound waves decrease the agglomerates of nanotubes producing conductive materials and static dissipators with a negative dielectric constant [66].…”
Section: Polymer Nanocomposite Focus Of the Study Property Improvemenmentioning
confidence: 71%
“…These authors concluded that the application of ultrasound improves the processability of the material and that it is possible to reduce the percentage of nanotubes in the preparation of nanocomposites with conductive properties without affecting thermal properties [53]. Ávila-Orta et al [51] used polypropylenes with different flow rates (MFI) and 10% multiwall carbon nanotubes for the preparation of nanocomposites. Four different fabrication methods based on melt extrusion were used.…”
Section: Polymer Nanocomposite Focus Of the Study Property Improvemenmentioning
confidence: 99%